2019
DOI: 10.1093/ckj/sfz017
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of adult cadaveric and live donor renal transplantation in the UK: a survey of national practice

Abstract: BackgroundThere is a limited evidence base and no national consensus regarding the perioperative management of patients undergoing renal transplantation. We developed an electronic survey to capture an overview of renal transplant perioperative practice across UK renal transplant centres and determine the need for future guidelines on patient management. MethodsA 29-question survey was developed to encompass the entire renal transplant perioperative pathway and input was sought from clinicians with expertise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The uptake of ERAS into the field of renal transplantation has been equally slow. In 2019, Morkane et al concluded that there was a high degree of heterogeneity between perioperative practises across 23 renal transplantation (RT) centres [69]. They found that 27.3% of centres utilised cardiac output measures to guide fluid administration, 40.9% aimed for specific intra-operative targets of central venous pressure, and 54.5% use fentanylbased patient-controlled anaesthesia alongside transversus abdominis plane block [69].…”
Section: Renal Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of ERAS into the field of renal transplantation has been equally slow. In 2019, Morkane et al concluded that there was a high degree of heterogeneity between perioperative practises across 23 renal transplantation (RT) centres [69]. They found that 27.3% of centres utilised cardiac output measures to guide fluid administration, 40.9% aimed for specific intra-operative targets of central venous pressure, and 54.5% use fentanylbased patient-controlled anaesthesia alongside transversus abdominis plane block [69].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…In 2019, Morkane et al concluded that there was a high degree of heterogeneity between perioperative practises across 23 renal transplantation (RT) centres [69]. They found that 27.3% of centres utilised cardiac output measures to guide fluid administration, 40.9% aimed for specific intra-operative targets of central venous pressure, and 54.5% use fentanylbased patient-controlled anaesthesia alongside transversus abdominis plane block [69]. This highlights the poor standardisation of perioperative care with regards to RT, despite evidence that enhanced recovery reduces length of hospital stay and confers better pain control than standard practices [70].…”
Section: Renal Transplantationmentioning
confidence: 99%
“…They identified a broad range of practice among 23 transplant centers in the United Kingdom with regard to intraoperative fluid management, blood pressure targets, vasopressor administration, central venous pressure monitoring, and pain management strategies. 15 Of note, 54.5% of centers performed TAP blocks, and 90.9% of centers provided patient-controlled analgesia (PCA) with fentanyl, morphine, or oxycodone (IV). Only a single center reported a renal transplant-specific ERAS program for cadaveric organ recipients.…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%
“…Only a single center reported a renal transplant-specific ERAS program for cadaveric organ recipients. 15 In our 2018 review, 16 we cited an initial implementation of an ERAS protocol for renal transplant recipients, which included 286 recipients in the ERAS group and 151 in the traditional recovery group, and showed significantly better pain control, decreased length of stay, and cost savings. 17 In 2019, Dias et al published the results of their standardized ERAS protocol with prospective data from July 2017 to December 2018 (N ¼ 100) and compared it with data from prior to ERAS implementation (N ¼ 100).…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%
“…In early stages of KT, urine production is considered to be a sign of successful reperfusion after anastomosis [8, 9]. The use of perioperative diuretics to increase urine volume differs among centers with respect to type and dose [10, 11]. Some reports have shown that long-term prognosis can be predicted by urine volume after KT [12, 13].…”
Section: Introductionmentioning
confidence: 99%